Immune-mediated inflammatory diseases with chronic excess of serum interleukin-18 - Miyazawa, Hanae; Wada, Taizo (Frontiers in Immunology, 2022)
Review: Interleukin-18 (IL-18) is a proinflammatory cytokine that promotes various innate immune processes related to infection, inflammation, and autoimmunity. Patients with systemic juvenile idiopathic arthritis and adult-onset Still’s disease exhibit chronic excess of serum IL-18, which is associated with a high incidence of macrophage activation syndrome (MAS), although the mechanisms of IL-18 regulation in such diseases remain largely unknown. Similar elevation of serum IL-18 and susceptibility to MAS/hemophagocytic lymphohistiocytosis (HLH) have been reported in monogenic diseases such as X-linked inhibitor of apoptosis deficiency (i.e., X-linked lymphoproliferative syndrome type 2) and NLRC4-associated autoinflammatory disease. Recent advances in molecular and cellular biology allow the identification of other genetic defects such as defects in CDC42, PSTPIP1, and WDR1 that result in high serum IL-18 levels and hyperinflammation. Among these diseases, chronic excess of serum IL-18 appears to be linked with severe hyperinflammation and/or predisposition to MAS/HLH. In this review, we focus on recent findings in inflammatory diseases associated with and probably attributable to chronic excess of serum IL-18 and describe the clinical and therapeutical relevance of understanding the pathology of this group of diseases.